Transvaginal strangulated bowel evisceration through uterine perforation due to unsafe abortion: a case report and literature review - Landry Wakheu Tchuenkam; Aimé Noula Mbonda; Joel Noutakdie Tochie; Patrick P. Mbem-Ngos; Hugues G. Noah-Ndzie; Guy Aristide Bang (BMC, 2021)
Abstract Background Induced abortion, whether therapeutic or elective, is a surgical procedure frequently practiced worldwide. It is a significant cause of maternal morbidity and mortality. When the procedure is performed in precarious conditions, by unqualified personnel, it leads to serious consequences, including uterine perforation and its associated lesions. Its management remains a medico-surgical emergency. Case presentation We present two cases of unsafe abortions performed by cervical dilatation and intrauterine curettage which resulted in uterine perforation and intestinal evisceration through the vagina leading to acute intestinal obstruction. Both patients underwent intensive resuscitation followed by an emergency laparotomy. The first case was a 26-year-old woman living in rural Cameroon. Following a procedure of termination of her pregnancy, the patient noted the presence of bowel at the vaginal introitus associated with signs of intestinal obstruction. She was transferred to a specialized center was after 4 days later of the onset of the evisceration. Considering the gangrened eviscerated terminal ileum, a right hemicolectomy with anastomosis was performed, as well as a suture of the uterine perforation. The second patient was an 18-year-old African living as a refugee in Cameroon. She was referred for abdominal pain in the context of intestinal obstruction with a viable jejunal loop extruding through the vagina. A simple jejunal resection was performed with end-to-end anastomosis and suture of the uterine perforation. In both cases, the postoperative course was uneventful. Conclusions Uterine perforation is a serious complication of intrauterine gynecological procedures and instrumental abortion in particular. It can lead to evisceration of the intra-abdominal viscera through the uterine perforation. It is therefore a real surgical emergency with multiple and fatal consequences.